Preparation method of germanium dual-band antireflection film system
By plating ZnS, Ge, YbF3 and Y2O3 film systems on both sides of the infrared optical lens, the problem of uneven transmittance in the 2-14 μm band in the prior art is solved, and the effect of low transmittance in the 2-5 μm band and high transmittance in the 7.5-14 μm band is achieved.
Patent Information
- Application Number
- CN202411632225.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-11-15
AI Technical Summary
The transmittance of existing infrared optical lenses in the 2-14μm band range is not uniform enough, making it difficult to meet the needs of different application ends.
Using germanium as the substrate, a nine-layer film system consisting of four films of ZnS, Ge, YbF3 and Y2O3 is plated on both sides of the lens through vacuum coating technology, ensuring that the transmittance in the 2-5μm band is less than 30% and the transmittance in the 7.5-14μm band is greater than 95%.
The transmittance in the 2-5μm band is achieved with a transmittance of less than 30% and a transmittance in the 7.5-14μm band is higher than 95%, meeting the demand for infrared transmittance at different applications.
Smart Images

Figure CN119506777A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to the field of infrared coating technology, and more specifically to a method for preparing a germanium dual-band anti-reflection film system. Background Art
[0002] In the field of infrared optical coatings, germanium has good infrared transmittance and refractive index, so it is often used in the manufacture of infrared optical lenses, infrared cameras, infrared telescopes, infrared sensors, infrared detectors and other equipment.
[0003] In the infrared detection band of 2-14μm, different applications will have different requirements for transmittance and its range, which requires further in-depth development. Summary of the invention
[0004] In view of the problems existing in the background technology, an object of the present invention is to provide a method for preparing a germanium dual-band anti-reflection film system, wherein the prepared germanium substrate coating sheet together with the film system on both sides has an average transmittance of less than 30% at 2-5μm and an average transmittance of greater than 95% at 7.5-14μm.
[0005] Thus, a method for preparing a germanium dual-band antireflection film system comprises the following steps: S1, cleaning the surface of the accompanying coating sheet and the product as the germanium substrate of the lens; S2, placing the treated lens into a fixture, and hanging the mounted lens into the cavity of a vacuum coating machine, and setting the temperature of the cavity to 150°C; S3, starting the vacuum coating machine to evacuate, and the vacuum degree reaches 1.5×10 -3Pa, turn on the Hall ion source of the vacuum coating machine for cleaning, the cleaning time is 6 minutes, the parameters of the Hall ion source are: anode voltage is 220V, anode current is 1.2A, neutralization current is 1.5A, neutralization gas flow rate is 10sccm, and argon gas flow rate is 100%; S4, on the first side of the lens, according to the nine-layer film system composed of four film materials of ZnS, Ge, YbF3 and Y2O3, 149nmZnS / 175.6nmGe / 488.4nmZnS / 107.8nmGe / 120nmZnS / 1150nmYbF3 / 182.5nmZnS / 100nmYbF3 / 10nmY2O3, the film layers are coated in sequence, among which Zn The numbers with nm before S, Ge, YbF3 and Y2O3 are the thickness of the corresponding film layers. The ZnS and YbF3 film layers are evaporated by resistance heating, and the Ge and Y2O3 film layers are evaporated by electron beam heating. The deposition rate of the ZnS film layer is 0.6nm / s, the deposition rate of the Ge film layer is 0.4nm / s, the deposition rate of the YbF3 film layer is 0.6nm / s, and the deposition rate of the Y2O3 film layer is 0.6nm / s. Each film layer is deposited with the assistance of an ion source, and each film layer is deposited at a chamber temperature of 150°C; S5, after the film system is coated on the first side of the lens, the chamber is naturally cooled to below 80°C, and the fixture is taken out together with the product; S7, repeat steps S1 to S6 to coat the same film system on the second side of the lens.
[0006] The beneficial effects of the present disclosure are as follows: According to the preparation method of the germanium dual-band anti-reflection film system of the present disclosure, through step S4 repeated by step S7, a nine-layer film system composed of four film materials of ZnS, Ge, YbF3 and Y2O3 (the two-sided film system constitutes the anti-reflection film system) is formed on the two sides of the lens, and combined with the surface cleaning of step S1 repeated by step S1 and step S7, the chamber temperature of step S2 repeated by step S2 and step S7, the ion source cleaning of step S3 repeated by step S7, and the cooling of step S5 repeated by step S7, as verified by Example 1 of the test process described later, the transmittance of the accompanying plate together with the film system on both sides is less than 30% (specifically 26%) at 2-5μm on average and greater than 95% (specifically 95.2%) at 7.5-14μm on average. BRIEF DESCRIPTION OF THE DRAWINGS
[0007] Figure 1 It is a curve chart of the transmittance of the accompanying coating sheet of Example 1 together with the film system coated on both sides. DETAILED DESCRIPTION
[0008] It will be understood that the disclosed embodiments are merely examples of the present disclosure, which may be implemented in various forms, and therefore, the specific details disclosed herein should not be interpreted as limiting, but merely as a basis for the claims and as a representative basis for teaching one of ordinary skill in the art to implement the present disclosure in various ways.
[0009] [Preparation method of germanium dual-band antireflection film system]
[0010] The method for preparing the germanium dual-band antireflection film system according to the present disclosure comprises the following steps:
[0011] S1, cleaning the surface of the accompanying plated sheet and the product as the germanium substrate of the lens;
[0012] S2, put the processed lens into the fixture, and hang the mounted lens into the vacuum coating machine cavity, and the temperature of the cavity is set to 150℃;
[0013] S3, vacuum coating machine starts to evacuate, and the vacuum degree reaches 1.5×10 -3 Pa, turn on the Hall ion source of the vacuum coating machine for cleaning, the cleaning time is 6 minutes, the parameters of the Hall ion source are: anode voltage is 220V, anode current is 1.2A, neutralization current is 1.5A, neutralization gas flow rate is 10sccm, and argon gas flow rate accounts for 100%;
[0014] S4, on the first side of the lens, a nine-layer film system consisting of four film materials: ZnS, Ge, YbF3 and Y2O3
[0015] 149nmZnS / 175.6nmGe / 488.4nmZnS / 107.8nmGe / 120nmZnS / 1150nmYbF3 / 182.5nmZnS / 100nmYbF3 / 10nmY2O3, sequentially deposit each film layer,
[0016] Among them, the numbers with nm before ZnS, Ge, YbF3 and Y2O3 are the film thicknesses of the corresponding films. The ZnS and YbF3 films are evaporated by resistance heating, and the Ge and Y2O3 films are evaporated by electron beam heating. The deposition rate of the ZnS film is 0.6 nm / s, the deposition rate of the Ge film is 0.4 nm / s, the deposition rate of the YbF3 film is 0.6 nm / s, and the deposition rate of the Y2O3 film is 0.6 nm / s. Each film layer is deposited by ion source assistance, and each film layer is deposited at a chamber temperature of 150°C.
[0017] S5, after the coating system of the first side of the lens is completed, the cavity is naturally cooled down to below 80°C, and the fixture and the product are taken out;
[0018] S7, repeating steps S1 to S6 to coat the second surface of the lens with the same coating system.
[0019] In the preparation method of the germanium dual-band anti-reflection film system according to the present disclosure, through step S4 repeated by step S7, a nine-layer film system composed of four film materials of ZnS, Ge, YbF3 and Y2O3 (the two-sided film system constitutes the anti-reflection film system) is formed on both sides of the lens, and combined with step S1 and step S7 repeated surface cleaning of step S1, step S2 and step S7 repeated cavity temperature of step S2, step S3 and step S7 repeated ion source cleaning of step S3 and step S7 repeated cooling of step S5, as verified by Example 1 of the test process described later, the transmittance of the accompanying plate together with the film system on both sides is less than 30% (specifically 26%) at 2-5μm on average and greater than 95% (specifically 95.2%) at 7.5-14μm on average.
[0020] The long-wave infrared band of 7.5-14μm is an atmospheric window. The atmosphere in this band hardly absorbs the infrared energy emitted by the object being measured, so generally long-wave detectors set the spectrum at this frequency in order to better receive the infrared energy emitted by the object being measured. Due to the absorption effect of the ground atmosphere, ground-based infrared telescopes (or detectors) can only observe from several atmospheric windows. 2-5μm is the beginning of the thermal infrared band and is the area where the L and M bands, important windows for ground observations, are located. The germanium substrate prepared by the method for preparing the germanium dual-band anti-reflection film system disclosed in the present invention, together with the film system on both sides, can be used for ground-based infrared astronomical detection.
[0021] The surface cleaning of step S1 repeated in step S7 is beneficial to improving the surface state of each surface of the lens, and is helpful to improve the bonding performance of the film system on each surface and the corresponding surface of the lens. For example, in step S1, the surface of the lens is cleaned by ultrasonic wave or hand rubbing. Further, for example, in step S1, the surface of the lens is cleaned by ultrasonic wave by polishing with aluminum oxide polishing liquid and then ultrasonic pure water cleaning. For example, the aluminum oxide polishing liquid uses 0.1μm polycrystalline diamond liquid of Nanjing Henry Precision Optics Co., Ltd.
[0022] In step S1 , for example, the thickness of the accompanying plating sheet is 1 mm.
[0023] The temperature setting of the vacuum coating machine in step S2 heats the lens through the cavity of the coating machine, which helps the growth of the film layer from the lens and reduces the film layer growth stress.
[0024] Step S3 uses a Hall ion source for cleaning, which will remove the impurities and oil molecules adsorbed on the surface of each surface of the lens, thereby greatly improving the interface state, which is helpful to improve the bonding performance between the film layer and the corresponding surface of the lens. At the same time, cleaning by the Hall ion source can heat the corresponding surface of the lens, which is helpful for the growth of the film layer from the lens and reduces the growth stress of the film layer. For example, the vacuum coating machine is a vacuum coating machine with a Hall ion source equipped with a neutralizer manufactured and sold by Chengdu Xiwok Vacuum Technology Co., Ltd., and the Hall ion source equipped with a neutralizer is purchased from Boton Optoelectronics Technology Co., Ltd.
[0025] In one example, in step S4, the ion source adopts a Hall ion source, and the ion source parameters when coating the ZnS film layer are: the neutralization current is 0.5A, the neutralization flow rate is 8sccm, the anode voltage is 120V, the anode current is 1.2A, and the argon flow rate accounts for 100%; the ion source parameters when coating the Ge film layer are: the neutralization current is 0.5A, the neutralization flow rate is 6-8sccm, the anode voltage is 120V, the anode current is 1A, and the argon flow rate accounts for 100%; When coating the YbF3 film, the ion source parameters are: neutralization current 0.5A, neutralization flow rate 10sccm, anode voltage 110V, anode current 1.2A, argon flow rate 30%, oxygen flow rate 70%; when coating the Y2O3 film, the ion source parameters are: neutralization current 0.5A, neutralization flow rate 6-8sccm, anode voltage 120V, anode current 1.2A, argon flow rate 30%, oxygen flow rate 70%.
[0026] In one example, in step S4, argon gas is introduced and vacuum is drawn to maintain a constant vacuum when each film layer is deposited, and the constant vacuum is set to be no less than 5.0×10 -3 Pa; use the crystal oscillator method to monitor the film thickness using the corresponding crystal oscillator of the multiple crystal oscillators of the crystal controller. After the ion source is cleaned, the crystal controller controls the corresponding operation of the new crystal oscillator among the multiple crystal oscillators, and the crystal oscillator frequency is not less than 5.99MHz.
[0027] [test]
[0028] Example 1
[0029] The method for preparing the germanium dual-band antireflection film system of Example 1 adopts the following steps:
[0030] S1, using ultrasonic cleaning to clean the surface of the accompanying plated sheet and the product as the germanium substrate of the lens. The surface cleaning of the lens using ultrasonic cleaning is polishing with aluminum oxide polishing liquid and then ultrasonic pure water cleaning. The aluminum oxide polishing liquid uses a 0.1μm polycrystalline diamond liquid produced by Nanjing Henry Precision Optics Co., Ltd.;
[0031] S2, placing the processed lens into a fixture, and hanging the mounted lens into the cavity of a vacuum coating machine, the temperature of the cavity is set to 150°C, the vacuum coating machine is a vacuum coating machine with a Hall ion source equipped with a neutralizer manufactured and sold by Chengdu West Work Vacuum Technology Co., Ltd., and the Hall ion source equipped with a neutralizer is purchased from Boton Optoelectronics Technology Co., Ltd.;
[0032] S3, vacuum coating machine starts to evacuate, and the vacuum degree reaches 1.5×10 -3 Pa, turn on the Hall ion source of the vacuum coating machine for cleaning, the cleaning time is 6 minutes, the parameters of the Hall ion source are: anode voltage is 220V, anode current is 1.2A, neutralization current is 1.5A, neutralization gas flow rate is 10sccm, and argon gas flow rate accounts for 100%;
[0033] S4, on the first side of the lens, a nine-layer film system consisting of four film materials: ZnS, Ge, YbF3 and Y2O3
[0034] 149nmZnS / 175.6nmGe / 488.4nmZnS / 107.8nmGe / 120nmZnS / 1150nmYbF3 / 182.5nmZnS / 100nmYbF3 / 10nmY2O3, sequentially deposit each film layer,
[0035] Among them, the numbers with nm before ZnS, Ge, YbF3 and Y2O3 are the film thicknesses of the corresponding films. The ZnS and YbF3 films are evaporated by resistance heating, and the Ge and Y2O3 films are evaporated by electron beam heating. The deposition rate of the ZnS film is 0.6 nm / s, the deposition rate of the Ge film is 0.4 nm / s, the deposition rate of the YbF3 film is 0.6 nm / s, and the deposition rate of the Y2O3 film is 0.6 nm / s. Each film layer is deposited by ion source assistance, and each film layer is deposited at a chamber temperature of 150°C.
[0036] In step S4,
[0037] The ion source adopts Hall ion source.
[0038] When coating the ZnS film, the ion source parameters are: neutralization current 0.5A, neutralization flow rate 8sccm, anode voltage 120V, anode current 1.2A, and argon flow rate 100%;
[0039] When depositing the Ge film, the ion source parameters are: neutralization current is 0.5A, neutralization flow rate is 7sccm, anode voltage is 120V, anode current is 1A, and argon flow rate accounts for 100%;
[0040] When coating the YbF3 film, the ion source parameters are: neutralization current 0.5A, neutralization flow rate 10sccm, anode voltage 110V, anode current 1.2A, argon flow rate 30%, oxygen flow rate 70%;
[0041] When the Y2O3 film is deposited, the ion source parameters are: neutralization current is 0.5A, neutralization flow rate is sccm, anode voltage is 120V, anode current is 1.2A, argon flow rate accounts for 30%, and oxygen flow rate accounts for 70%;
[0042] When depositing each film layer, argon gas was introduced and vacuum was evacuated to maintain the flow type constant vacuum, and the constant vacuum degree was set to 5.0×10 -3 Pa;
[0043] The crystal oscillator method is used to monitor the film thickness using the corresponding crystal oscillator of the multiple crystal oscillators of the crystal controller. After the ion source is cleaned, the crystal controller controls the corresponding operation of the new crystal oscillator of the multiple crystal oscillators, and the crystal oscillator frequency is 5.99MHz.
[0044] S5, after the coating system on the first side of the lens is completed, the cavity is naturally cooled to 80°C, and the fixture and the product are taken out;
[0045] S7, repeating steps S1 to S6 to coat the second surface of the lens with the same coating system.
[0046] Figure 1 It is a curve diagram of the transmittance of the accompanying coating sheet of Example 1 together with the film system coated on both sides. Figure 1 It can be seen that the transmittance of the accompanying plate together with the films on both sides is less than 30% (specifically 26%) at 2-5 μm on average and greater than 95% (specifically 95.2%) at 7.5-14 μm on average.
[0047] The following tests are carried out on the accompanying plating sheet and the films on both sides.
[0048] Water bubble test: The accompanying plating sheet prepared in Example 1 together with the films on both sides were subjected to a water bubble test with tap water for 10 minutes. No film system on each side was found to fall off the accompanying plating sheet, and no film system on each side was found to be cracked.
[0049] Adhesion test: After the bubble test with tap water is completed, the 3M tape is pasted on the film system on each side of the product by hand and the tape is pulled in the direction opposite to the pasting end, and the film system on each side is not pulled up.
[0050] The water bubble test and adhesion test show that the film system on each surface of the plating sheet has good adhesion.
[0051] The above detailed description is used to describe multiple exemplary embodiments, but this document is not intended to be limited to the explicitly disclosed combinations. Therefore, unless otherwise stated, the various features disclosed herein can be combined together to form multiple additional combinations that are not shown for the sake of simplicity.
Claims
1. A method for preparing a germanium dual-band anti-reflection film system, characterized in that: Includes steps: S1, cleaning the surface of the accompanying plated sheet and the product as the germanium substrate of the lens; S2, put the processed lens into the fixture, and hang the mounted lens into the vacuum coating machine cavity, and the temperature of the cavity is set to 150℃; S3, vacuum coating machine starts to evacuate, and the vacuum degree reaches 1.5×10 -3 Pa, turn on the Hall ion source of the vacuum coating machine for cleaning, the cleaning time is 6 minutes, the parameters of the Hall ion source are: anode voltage is 220V, anode current is 1.2A, neutralization current is 1.5A, neutralization gas flow rate is 10sccm, and argon gas flow rate accounts for 100%; S4, on the first side of the lens, a nine-layer film system consisting of four film materials: ZnS, Ge, YbF3 and Y2O3 149nmZnS / 175.6nmGe / 488.4nmZnS / 107.8nmGe / 120nmZnS / 1150nmYbF3 / 182.5nmZnS / 100nmYbF3 / 10nmY2O3, sequentially deposit each film layer, Among them, the numbers with nm before ZnS, Ge, YbF3 and Y2O3 are the film thicknesses of the corresponding films. The ZnS and YbF3 films are evaporated by resistance heating, and the Ge and Y2O3 films are evaporated by electron beam heating. The deposition rate of the ZnS film is 0.6 nm / s, the deposition rate of the Ge film is 0.4 nm / s, the deposition rate of the YbF3 film is 0.6 nm / s, and the deposition rate of the Y2O3 film is 0.6 nm / s. Each film layer is deposited by ion source assistance, and each film layer is deposited at a chamber temperature of 150°C. S5, after the coating system of the first side of the lens is completed, the cavity is naturally cooled down to below 80°C, and the fixture and the product are taken out; S7, repeating steps S1 to S6 to coat the second surface of the lens with the same coating system.
2. The method for preparing the germanium dual-band antireflection film system according to claim 1, characterized in that: In step S1, the surface of the lens is cleaned by ultrasonic wave or hand wiping.
3. The method for preparing the germanium dual-band antireflection film system according to claim 1, characterized in that: In step S1, the surface of the lens is cleaned by ultrasonic wave by polishing with aluminum oxide polishing liquid and then by ultrasonic pure water cleaning.
4. The method for preparing the germanium dual-band antireflection film system according to claim 3, characterized in that: In step S1, the aluminum oxide polishing liquid adopts the 0.1 μm polycrystalline diamond liquid produced by Nanjing Henry Precision Optics Co., Ltd.
5. The method for preparing a germanium dual-band antireflection film system according to claim 1, characterized in that: The thickness of the accompanying plating sheet is 1mm.
6. The method for preparing a germanium dual-band antireflection film system according to claim 1, characterized in that: In step S4, The ion source adopts Hall ion source. When coating the ZnS film, the ion source parameters are: neutralization current 0.5A, neutralization flow rate 8sccm, anode voltage 120V, anode current 1.2A, and argon flow rate 100%; When depositing the Ge film, the ion source parameters are: neutralization current is 0.5A, neutralization flow rate is 6-8sccm, anode voltage is 120V, anode current is 1A, and argon flow rate accounts for 100%; When coating the YbF3 film, the ion source parameters are: neutralization current 0.5A, neutralization flow rate 10sccm, anode voltage 110V, anode current 1.2A, argon flow rate 30%, oxygen flow rate 70%; When coating the Y2O3 film layer, the ion source parameters are: neutralization current is 0.5A, neutralization flow rate is 6-8sccm, anode voltage is 120V, anode current is 1.2A, argon flow rate accounts for 30%, and oxygen flow rate accounts for 70%.
7. The method for preparing a germanium dual-band antireflection film system according to claim 1, characterized in that: In step S4, When coating each film layer, argon gas is introduced and vacuum is drawn to maintain the flow type constant vacuum, and the constant vacuum is set to no less than 5.0×10 -3 Pa; The crystal oscillator method is used to monitor the film thickness using the corresponding crystal oscillator pieces of the multiple crystal oscillator pieces of the crystal controller. After the ion source is cleaned, the crystal controller controls the corresponding operation of the new crystal oscillator pieces among the multiple crystal oscillator pieces, and the crystal oscillator frequency is not less than 5.99MHz.
Citation Information
Patent Citations
Medium-wave infrared anti-reflection film design and preparation method
CN110794490A
Preparation method for plating antireflection film system on chalcogenide glass substrate
CN116282962A
Medium-wave infrared anti-reflection film suitable for wide-angle incidence and preparation method of medium-wave infrared anti-reflection film
CN117761806A
Preparation method of 8-12 [mu] m antireflection film system on chalcogenide glass substrate
CN118880250A